3-O-Methyldopa inhibits astrocyte-mediated dopaminergic neuroprotective effects of l-DOPA. Issue 1 (December 2016) - Asanuma, Masato; Miyazaki, Ikuko
Abstract Background We evaluated the effects of 3-O -methyldopa (3-OMD), a metabolite ofl -DOPA which is formed by catechol-O -methyltransferase (COMT), on the uptake, metabolism, and neuroprotective effects ofl -DOPA in striatal astrocytes. We examined changes in the numbers of dopaminergic neurons after treatment withl -DOPA and 3-OMD or entacapone, a peripheral COMT inhibitor, using primary cultured mesencephalic neurons and striatal astrocytes. Results The number of tyrosine hydroxylase-positive dopaminergic neurons was not affected byl -DOPA treatment in mesencephalic neurons alone. However, the increase in viability of dopaminergic neurons in the presence of astrocytes was further enhanced after methyl-l -DOPA treatment (25 µM) in mixed cultured mesencephalic neurons and striatal astrocytes. The neuroprotective effect of 25 µM l -DOPA was almost completely inhibited by simultaneous treatment with 3-OMD (10 or 100 µM), and was enhanced by concomitant treatment with entacapone (0.3 µM). The uptake ofl -DOPA into and the release of glutathione from striatal astrocytes afterl -DOPA treatment (100 µM) were inhibited by simultaneous exposure to 3-OMD (100 µM). Conclusions These data suggest thatl -DOPA exerts its neuroprotective effect on dopaminergic neurons via astrocytes and that 3-OMD competes withl -DOPA by acting on target molecule(s) (possibly including glutathione) released from astrocytes. Since some amount of entacapone can cross the blood–brain barrier, this reagent may enhancel -DOPA transportation by inhibiting COMT and increase the astrocyte-mediated neuroprotective effects ofl -DOPA on dopaminergic neurons.